Álbum seriado sobre amamentação baseado na teoria interativa de amamentação: estudo de validação e intervenção - Cantalejo, Thamires Fontoura (2024)
Introduction: Breastfeeding is a natural physiological process, but it is influenced by numerous factors that make it difficult to adhere to and continue breastfeeding. In Brazil, the prevalence of exclusive breastfeeding has a median duration of only three months, which reinforces the need to employ strategies and strengthen public policies in favor of a return to the practice of breastfeeding. Objective: To validate the appearance of the serial album on breastfeeding; to assess the knowledge of pregnant women in relation to breastfeeding; to assess the effect of the application of the serial album on the knowledge of pregnant women about breastfeeding. Method: In the first stage, an appearance evaluation study was carried out and, in the second stage, a quasi-experimental, longitudinal study, in which a single group was evaluated in terms of their knowledge of breastfeeding before and after an intervention using the serial album. The study was carried out at a university hospital run by the Brazilian Hospital Services Company (EBSERH). The evaluation of the appearance of the serial album was carried out with pregnant and postpartum women admitted to the hospital's maternity ward and the intervention stage used the serial album with pregnant women undergoing prenatal care at the outpatient clinic attached to the hospital. Results: In the appearance evaluation stage with the target audience, the sample consisted of 101 participants including puerperal and pregnant women, who evaluated the album in terms of its objective, organization, writing style, appearance and motivation, obtaining an Appearance-Total Validity Index of 0.94, considered excellent. A total of 26 pregnant women undergoing prenatal care took part in the intervention using the serial album on breastfeeding. The knowledge analysis carried out with the study participants revealed that the level of knowledge ranged from intermediate to adequate before the intervention and 30 days after the intervention the number of correct answers increased, with most of the pregnant women reaching an adequate level of knowledge. Conclusion: The serialized breastfeeding album based on the Interactive Breastfeeding Theory was validated in terms of its appearance by pregnant and postpartum women and contributed positively to increasing the level of knowledge about breastfeeding.